2014
DOI: 10.5194/nhess-14-1871-2014
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary approach to volcanic risk reduction under conditions of uncertainty: a case study of Tristan da Cunha

Abstract: Abstract. The uncertainty brought about by intermittent volcanic activity is fairly common at volcanoes worldwide. While better knowledge of any one volcano's behavioural characteristics has the potential to reduce this uncertainty, the subsequent reduction of risk from volcanic threats is only realised if that knowledge is pertinent to stakeholders and effectively communicated to inform good decision making. Success requires integration of methods, skills and expertise across disciplinary boundaries.This rese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Gehl et al (2013, in this special issue) have devised a tool to calculate damage caused by a given potential eruption, using eruptive scenarios fed by a hypothesized chronology of adverse events. Then, they use state of the art fragility functions (e.g., Jenkins et al, 2014) to evaluate the damage to vulnerable infrastructures (buildings, agriculture, roads, water or electrical networks). The tool was implemented at Mount Cameroon volcano, using data previously collected by Thierry et al (2008), who formerly showed that risk scenarios can help authorities in charge of crisis management to prepare for future events.…”
Section: New Approaches and Methods For Volcanoes Where Limited Knowlmentioning
confidence: 99%
“…Gehl et al (2013, in this special issue) have devised a tool to calculate damage caused by a given potential eruption, using eruptive scenarios fed by a hypothesized chronology of adverse events. Then, they use state of the art fragility functions (e.g., Jenkins et al, 2014) to evaluate the damage to vulnerable infrastructures (buildings, agriculture, roads, water or electrical networks). The tool was implemented at Mount Cameroon volcano, using data previously collected by Thierry et al (2008), who formerly showed that risk scenarios can help authorities in charge of crisis management to prepare for future events.…”
Section: New Approaches and Methods For Volcanoes Where Limited Knowlmentioning
confidence: 99%
“…This underpinning data included: (i) historical analyses of previous eruptions in St Vincent (Pyle, Barclay and Armijos 2017); (ii) group discussion data from earlier STREVA 'forensic' 6 workshops held in St Vincent and Colombia in 2014 ; (iii) interview data with project partners and communities (Armijos and Few 2016, Wilkinson et al 2016, and (iv) learning from other volcanic settings (e.g. Montserrat and Ecuador) (Hicks and Few 2015, Wilkinson 2015, Stone et al 2014, Hicks et al 2014, Few, Armijos and Barclay 2017. The breadth and depth of data, as well as our strong relationships with communities in both settings, was essential to position the films within each specific socio-cultural context and to ensure the aims of the films were both relevant to, and met the needs of the audience.…”
Section: Conceptmentioning
confidence: 99%
“…the likelihood of physical exposure to the hazard) and, while this is an important component of volcanic risk analysis, it needs to be supported by further research to identify the differentiation and dynamics of societal vulnerability to volcanic hazards (e.g., Dibben and Chester 1999;Wisner et al 2004). Further, empirical research that integrates vulnerability data into volcanic risk assessments is virtually absent (as an exception, see Hicks et al 2014). This is likely a function of, a) the complexity of integrating qualitative and quantitative data sets; b) the challenges of effectively working in an interdisciplinary team to produce new knowledge, when disciplinary methodologies and epistemologies are seemingly incompatible, and c) a disciplinary mismatch of required time for data gathering (social scientific data, for example, usually requires a longer time to obtain than many forms of physical scientific data).…”
Section: Assessing Vulnerability In Volcanic Settingsmentioning
confidence: 99%